State of the art of the Latin American HIV/Aids epidemic after 30 years theonset - Alonso, Mónica; Montesdeoca, Yaiza Rivero (Tempus – Actas de Saúde Coletiva, 2010)
The authors make a careful review of available information on the HIV/aids epidemics in Latin America. 4 ey start from the characteristics of the epidemic in the región, which is restricted to certain groups of population, and they describe the situation among those groups, some of them de' ned by their behavior (MSM,IDU, commercial sex workers), or special situations (incarcerated men, migrants), reaching a more open population (women, youth). Descriptions are illustrated with results of seroprevalence studies. Also they report the decline in the condom use prevalence among CSW as they become older, but these prevalences are higher than the obtained among men who have comercial sex with other men (less than 50% have safe sex).